On the effect of cobalt loading on catalytic activity of Co-BEA zeolites in ethane oxidative dehydrogenation and ammoxidation - Novoveská, Kateřina; Bulánek, Roman; Wichterlová, Blanka (Univerzita Pardubice, 2004)
Metal ion species introduced into zeolite seem to be attractive redox catalysts. There is a great effort to convert light paraffins into more valuable chemicals. Zeolites of BEA type modified by cobalt exhibited the highest activity and selectivity in ammoxidation and oxidative dehydrogenation of ethane in comparison with other high-silica zeolite matrices modified by cobalt. In this paper a set of sample with different cobalt loading has been prepared and their catalytic activity was compared. It was found that the catalytic activity was increased with the increasing cobalt concentration up to molar ratio Co/Al 0.5 in oxidative dehydrogenation. At higher level of ion exchange there was observed a dramatic decrease in activity, , which can be ascribed to formation of oxide clusters of cobalt. Cobalt oxides cause the non-seslctive oxidation of ethane to carbon oxides. On the contrary, in ammoxidation of ethane the catalysts exhibited the activity independent of cobalt content up to Co/Al molar ratio 0.4, which is much higher than activity in oxidative dehydrogenation. This enhanced activity is explained by formation of ammonia adsorption complexes or presence of reactive surface oxygen rising from decomposition of nitrous oxide produced by oxidation of ammonia. At high cobalt loading the activity has the similar history as in oxidative dehydrogenation of ethane. Besides bare cobalt ions and cobalt oxide clusters, the oxygen bridged cobalt dimers are formed in the Co-BEA zeolites with cobalt loading close to theoretical exchange level. These complexes exhibit specific reactivity, which differs from both highly dispersed cobalt oxide and atomically dispersed CO2+ ions in the cationic site of BEA framework.